2009
DOI: 10.1093/sleep/32.2.159
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled, Crossover Study of Xp13512/Gsk1838262 in the Treatment of Patients With Primary Restless Legs Syndrome

Abstract: XP13512 1800 mg/day significantly reduced RLS symptoms, improved sleep, and was generally well tolerated in subjects with moderate-to-severe primary RLS across 14 days of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 34 publications
3
63
0
Order By: Relevance
“…Gabapentin enacarbil is a slow-release gabapentin prodrug. It is highly likely that gabapentin enacarbil decreases IRLS scores (4 Class I studies with different study durations [35][36][37][38] ). It is highly likely that gabapentin enacarbil improves subjective sleep measures (4 Class I studies [35][36][37][38] ) and likely that it improves at least some objective sleep measures other than the PLMI (1 Class I study 35 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gabapentin enacarbil is a slow-release gabapentin prodrug. It is highly likely that gabapentin enacarbil decreases IRLS scores (4 Class I studies with different study durations [35][36][37][38] ). It is highly likely that gabapentin enacarbil improves subjective sleep measures (4 Class I studies [35][36][37][38] ) and likely that it improves at least some objective sleep measures other than the PLMI (1 Class I study 35 ).…”
mentioning
confidence: 99%
“…It is highly likely that gabapentin enacarbil decreases IRLS scores (4 Class I studies with different study durations [35][36][37][38] ). It is highly likely that gabapentin enacarbil improves subjective sleep measures (4 Class I studies [35][36][37][38] ) and likely that it improves at least some objective sleep measures other than the PLMI (1 Class I study 35 ). Because results of this Class I study were not statistically significant and CIs included both potentially clinically important and unimportant effects, there is insufficient evidence to support or refute the effect of gabapentin enacarbil on the PLMI.…”
mentioning
confidence: 99%
“…The two most common AEs, dizziness and somnolence, occurred at rates similar to those reported in previous studies of GEn in RLS. 20,21,30 Importantly, ESS findings indicated that increased daytime sleepiness did not occur with either GEn dose, despite reports of somnolence as an AE. The ESS questionnaire is designed to evaluate daytime sleepiness; questions on the ESS focus on the likelihood of dozing in any given situation and the impact this has on daytime activities.…”
Section: Discussionmentioning
confidence: 97%
“…Sample size was determined for each of the co-primary endpoints using the results of 2 previous GEn studies 21,30 ; 105 subjects per treatment group were considered sufficient to detect with 90% power, a mean treatment difference (GEn 1200 mg compared with placebo) of −4.0 in mean change from baseline in IRLS total score at the 0.05 significance level using a 2-sided t-test, assuming a standard deviation (SD) of 8.8, and a difference in response rate of 23% on the investigator-rated CGI-I (GEn 68%, placebo 45%; odds ratio [OR] 2.6). Positive evidence of efficacy required both co-primary tests to be significant (p < 0.05).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Many studies [123][124][125][126][127][128][129] have demonstrated its effectiveness and safety for RLS patients in North America and Europe, whereas 1 recent study has demonstrated similar results for Japanese patients [130]. This drug is a pro-drug of gabapentin, which possesses a side chain (see Fig.…”
Section: Gabapentinmentioning
confidence: 99%